Pattern of fatal injury in fall from height cases- a medicolegal study (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: In occupational settings, the most common type of fatal accident is fall from a height. The skull, brain, spinal cord and extremities are the most commonly injured systems. Falls from more than 20 feet have historically been triaged to trauma centers but even low-level falls can cause serious head injuries and death. Objectives: The objective of this study was to find out the pattern of injuries and related medico-legal issues among the victims of fall from height. Methods: This retrospective study was conducted among the victims of fall from height at Dhaka Medical College morgue during the period of January to December 2008.Various data were collected from inquest reports submitted by the investigating officers. Specific points regarding injuries were noted during autopsy examinations. Results: A total 2714 autopsies were performed during the study period out of which 93(3.43%) were cases of fall from height. Among them 66(70.97%) were male and 27(29.03%) victims were female. Most of the victims 23(24.73%) were day labourer/ construction workers. Minimum level of height of fall was from 2nd floor 7(7.52%) and maximum number of victim have fallen from 5th to 10th floor 47(50.53%). Considering timing, highest incidents occurred during day time 57(61.29%). Ages of maximum victims were between 21-30 years 34(36.56%). All the victims had multiple abrasions and bruises in their body, followed by laceration 74(79.56%), fracture of skull 57(61.29%) 80 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 intra cranial haemorrrhage 85(91.40%), injury to long bones of lower limbs 47(50.54%), injury to long bones of upper limbs 31(33.33%), injury to abdominal organs like liver, spleen, kidney 51(54.84%), fracture of pelvis 37(39.78%). In skull, linear fracture was the commonest one 48(51.61%), Temporal bone was the commonest bone to fracture 57(61.29%) and most of the victims 57(61.29%) had sub dural haemorrhage. Conclusion: Death due to fall from height is an unforeseen and unfortunate occurrence. Installation of window guard, modification of physical environment, maintenance of safety as per building construction code, parental counseling to children can reduce this economical burden and protect vulnerable groups of people of our country from this type of incidents. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22930 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014